2013
DOI: 10.1111/jnc.12455
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin‐2 in nervous system disorders

Abstract: Dynamin-2 is a pleiotropic GTPase whose best-known function is related to membrane scission during vesicle budding from the plasma or Golgi membranes. In the nervous system, dynamin-2 participates in synaptic vesicle recycling, postsynaptic receptor internalization, neurosecretion, and neuronal process extension. Some of these functions are shared with the other two dynamin isoforms. However, the involvement of dynamin-2 in neurological illnesses points to a critical function of this isoform in the nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 137 publications
(210 reference statements)
0
40
0
Order By: Relevance
“…Human mutations in DRP1 or DYN2 have been associated with neurological impairments (Gonzalez-Jamett et al, 2014; Vanstone et al, 2016; Waterham et al, 2007). Drp1, despite lacking a transmembrane domain, cycles from the cytosol to spots on the mitochondrial outer membrane (Smirnova et al, 1998) by interacting with several proteins, including Fis1, Mff, MiD49, MiD51 and a BAR-domain protein endophilin B1 (Cerveny et al, 2001; Cherok et al, 2017; Fekkes et al, 2000; Gandre-Babbe and van der Bliek, 2008; Otera et al, 2010; Palmer et al, 2011; Tieu and Nunnari, 2000; Zhao et al, 2011).…”
Section: Cellular Machinery Of Mitochondrial Fissionmentioning
confidence: 99%
“…Human mutations in DRP1 or DYN2 have been associated with neurological impairments (Gonzalez-Jamett et al, 2014; Vanstone et al, 2016; Waterham et al, 2007). Drp1, despite lacking a transmembrane domain, cycles from the cytosol to spots on the mitochondrial outer membrane (Smirnova et al, 1998) by interacting with several proteins, including Fis1, Mff, MiD49, MiD51 and a BAR-domain protein endophilin B1 (Cerveny et al, 2001; Cherok et al, 2017; Fekkes et al, 2000; Gandre-Babbe and van der Bliek, 2008; Otera et al, 2010; Palmer et al, 2011; Tieu and Nunnari, 2000; Zhao et al, 2011).…”
Section: Cellular Machinery Of Mitochondrial Fissionmentioning
confidence: 99%
“…Eight CMT-associated mutations in dynamin 2 have been reported to date [9]. These mutations occur mainly at the PH domain, which is the binding motif for phosphoinositide binding.…”
Section: Expression Of a Dynamin 2 Mutant Associated Withmentioning
confidence: 99%
“…These mutations occur mainly at the PH domain, which is the binding motif for phosphoinositide binding. Mutations have also been detected in the middle and PRD domains [9]. Analysis of fibroblasts derived from CMT patients or cells expressing CMT mutant dynamin 2 showed that mutations in the PH domain lead to defective endocytosis of surface receptors, including EGF and transferrin receptors [10,11].…”
Section: Expression Of a Dynamin 2 Mutant Associated Withmentioning
confidence: 99%
“…7 Dynamin-2 is one of 3 isoforms of dynamin, and acts as a GTPase involved in endocytosis and membrane remodeling. 12,13 Their major role is in membrane fission, but there is an expanding number of functions attributed to the dynamin proteins, such as microtubule and cytoskeletal maintenance, transportation of molecules from organelles like the Golgi apparatus, and calcium homeostasis. 11,12 Mutations in DNM2 can also cause intermediate and axonal dominant forms of Charcot-Marie-Tooth neuropathy (CMT).…”
Section: Sectionmentioning
confidence: 99%
“…12,13 Their major role is in membrane fission, but there is an expanding number of functions attributed to the dynamin proteins, such as microtubule and cytoskeletal maintenance, transportation of molecules from organelles like the Golgi apparatus, and calcium homeostasis. 11,12 Mutations in DNM2 can also cause intermediate and axonal dominant forms of Charcot-Marie-Tooth neuropathy (CMT). The mutations associated with CNM tend to occur in different locations within the DNM2 gene than those associated with CMT.…”
Section: Sectionmentioning
confidence: 99%